Nathrius brevipennis (Mu1sant 1839) (Col.: Cerambycidae) in Greece - Santas, L.A. (ENTOMOLOGIA HELLENICA, 1984)
In the spring of 1975, the trees of an almond orchard [Prunus dulcis (Miller) D.A. Webb] in Avliotes Corfu, were found to be severely infested by a wood borer insect in the larval stage. Samples of infested with larvae twigs, preserved in the laboratory, and in the same year in September a number of adults emerged. After identification this insect was found to be Nathrius (Leptidea) brevipennis (Mulsant 1839). This species caused important damage in the almond trees of the Avliotes area of Corfu during the years 1975-1976. In 1977, N. brevipennis was found in Ioannina county on walnut trees (Juglans regia L.) and in 1980, it was found in Metsovo area on almond trees.